Ehl-i Şam, İmam Evzai ve usul düşüncesi - Ekşici, Abdülmecid Yasir (My University, 2014)
Fıkıh tarihi, teşekkül dönemi, ehl-i Şam, fakih, Evzâî, Mekhûl, usûl, deliller, amel. ÖZET EHL-İ ŞAM, İMAM EVZÂÎ VE USÛL DÜŞÜNCESİ Teşekkül döneminin önemli ilim merkezlerinden biri olan Şam’daki ilmî muhit ve bu muhitin mümessilleri yani ehl-i Şam hakkındaki malumatımız oldukça genel ve sınırlıdır. Bu araştırmada ehl-i Şam’ın keşfine ve bu muhitin en meşhur fakihi olan İmam Evzâî ve onun fıkıh düşüncesinin tetkikine çalışılmıştır. Tez iki bölümden müteşekkildir. İlk bölümde erken dönem ilim merkezlerinden biri olan Şam’ın ilmî serüveni hakkında, sahâbe, tâbiîn ve tebe-i tâbiîn dönemlerini içine alan bir tasvir yapılması ve böylece tebe-i tâbiîn neslinden olan İmam Evzâî ve düşüncesi için bir zemin oluşturulması amaçlanmıştır. Bu çerçevedeki tetkikler sayesinde ehl-i Medine ve ehl-i Kûfe’ye nispetle oldukça müphem olan ehl-i Şam’a ışık tutulmuş ve dikkate değer sonuçlara ulaşılmıştır. İkinci bölümde ise önce ehl-i Şam’ın en meşhur âlimi olan ve müctehid imamlar arasında yer alan Evzâî’nin ilmî şahsiyeti ekseninde biyografisi işlenmiş, ardından onun usûl anlayışı ana hatlarıyla tespit ve tahlil edilmeye çalışılmıştır. story of Fiqh, Formation Period, Ahl Sham, Faqih, Awzai, Makhoul, Methodology, Proofs, Deed (Amal)

AHL SHAM, IMAM AWZAİ AND HIS THOUGHT ON METHODOLOGY Our knowledge of one of the important centers of learning during the formation period, Damascus, and about its’ main proponents, in other words Ahl al-Sham, remains considerably general and limited. This research tries to further explore and analyze ahl al-Sham, and more specifically the most famous faqih of this center, namely Imam Awzai and his legal thought. The dissertation consists of two parts. The first part aims to provide a basis for Imam Awzai who belongs to the generation of the followers of the Companions, and his thought, by describing the scholarly history of one of the most important centers of learning during the formation period, Damascus. This description includes the periods of the companions, the followers and the followers of the followers. Through the examination within this framework, a new light is shed on ahl al-Sham, which in comparison to ahl al-Madina and ahl al-Kufa is considerably unknown, and significant conclusions are reached. In the second part the biography of ahl al-Sham’s most famous scholar, al-Awzai, who is considered among the mujtahid imams, is treated in line with his scholarly personality. Finally, his thought on legal methodology is identified and analyzed in a general manner.
Keywords: İslam hukuku; Suriye; Şam; Tarih